Interpersonal problems, emotional facial expression recognition, and alcoholism. - Koehler, Vinicius Betzel (2020)
Interpersonal problems and emotional facial expression recognition (EFER) impairments have been vastly reported to be present in Alcoholics. Despite the international scientific interest in studying the relationship of these variables on this population,